FIGURATIVE LANGUAGE IN SELECTED SONGS OF “RED” BY TAYLOR SWIFT - Fatikha, Alya Rizqi; Masykuroh, Qanitah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This study aims to explore the types and meanings of figurative language in Taylor Swift’s song lyrics. On the surface level, figurative language cannot be translated literally. The study is descriptive qualitative, and the data are in the forms of figurative language taken from eight selected songs in Taylor Swift's album "Red" collected by documentation technique. The data are then analyzed using content analysis by referring to the framework of Knickerbocker Reninger’s theory (1985) on figurative language. From the analysis, there are 57 types of figurative language in the selected songs, namely hyperbole 31,5%, simile 19,3%, metaphor 17,5%, metonymy 5,3%, irony 3,5%, symbol 7,0%, personification 10,6%, paradox 3,5% and synecdoche 1,8%. Furthermore, the meaning of each figurative language used in the song lyrics is contextually explored and allied with the content of the song lyrics which conveys the various deep expressions of feeling and emotion of Taylor Swift as both a singer and a songwriter.